1999
DOI: 10.1177/152660289900600310
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Endoluminal Grafting for Aneurysmal and Occlusive Disease in the Superficial Femoral Artery

Abstract: Purpose: To examine the long-term outcome of patients treated with endoluminal grafts (ELGs) for aneurysmal and occlusive disease in the femoropopliteal (FP) segment. Methods: ELGs of radially expandable polytetrafluoroethylene with terminal Palmaz stents were used to form intimal conduits to revascularize lengthy occlusive disease and exclude aneurysms in the FP segment. Patient records were reviewed retrospectively for outcome. Results: Fifty-five (98%) of 56 ELGs were placed successfully in 51 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…The safety and efficacy of endovascular stent-grafts have been demonstrated in a variety of peripheral arterial pathologies, including trauma and aneurysmal disease. 6,7,[11][12][13][14] In our study, primary technical success was achieved in all 20 consecutive cases, confirming that implantation of covered stents is highly effective in repairing traumatic arterial lesions and re-establishing the vascular integrity of the injured vessel. Angiography and CT scans have clearly demonstrated that the initial effect was maintained over a median 21month follow-up.…”
Section: Discussionsupporting
confidence: 59%
“…The safety and efficacy of endovascular stent-grafts have been demonstrated in a variety of peripheral arterial pathologies, including trauma and aneurysmal disease. 6,7,[11][12][13][14] In our study, primary technical success was achieved in all 20 consecutive cases, confirming that implantation of covered stents is highly effective in repairing traumatic arterial lesions and re-establishing the vascular integrity of the injured vessel. Angiography and CT scans have clearly demonstrated that the initial effect was maintained over a median 21month follow-up.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, covered stents may have an advantage over bare metal stents, and some authors have made such an observation. [31][32][33] Although reported results with Hemobahn and Viabahn stent grafts have been encouraging, [31][32][33][34][35][36][37][38][39][40][41][42][43] there have been no reports of direct comparison to outcomes with uncovered stents. This information void is the basis of the VIBRANT trial that will compare results with uncovered metal to Viabahn stents for TASC C and D disease in the SFA.…”
Section: Discussionmentioning
confidence: 99%
“…At present, new endovascular stent-graft systems are being developed (8,11,12). To enable comparison of the results of a new therapy with established therapies, data on benefits and costs of the established procedures must be available.…”
mentioning
confidence: 99%